A Third-Order Consensus Approach for Vehicle Platoon with Intervehicle Communication - Jianzhong Chen; Dongyang Bai; Huan Liang; Yang Zhou (Journal of Advanced Transportation)
A third-order consensus approach is proposed for the vehicle platoon. For addressing the platoon problem, a realistic, third-order vehicle dynamics model is used, and the spacing policy and the vehicle acceleration error are embedded into the consensus protocol. A sufficient and necessary condition of asymptotically stability is obtained for the vehicle platooning system. Numerical simulations for several traffic scenarios are carried out. The results demonstrate the effectiveness and the robustness of the presented approach.